Impact of crude palm oil export duties on Malaysian palm oil industry - Ibragimov, Abdulla Gafurjanovich (2014)
Malaysia and Indonesia are the world’s largest producers of palm oil. Both countries export crude and processed palm oil. Since Malaysia and Indonesia are close competitors and they compete in the same market, a change in export duty rate in one country will affect the other. Indonesia, as the world's biggest palm oil producer, has drastically widened the gap between the crude palm oil and refined palm oil export taxes since October 2011, to encourage more downstream investments and production of refined palm oil products. Under the revised export duty structure, crude palm oil and crude palm kernel oil are cheaper for downstream activities in Indonesia. The new structure is expected to reduce Malaysia’s competitiveness in the world market as its export duty is relatively higher. Realizing this fact, Malaysia has reduced the export duty structure to be in line with the Indonesia’s duty structure (MPOB, 2013). The general objective of the study is to examine the impact of export tariffs on Malaysian palm oil industry. The specific objectives are (i) to examine the impact of changes in the Malaysian export tariffs on palm oil production; (ii) to examine the impact of changes in the Malaysian export tariffs on exports of crude palm oil and processed palm oil; and (iii) to simulate scenarios under different levels of export duty. The research questions are: (i) what are the likely future trends of crude palm oil exports under the new crude palm oil export duties? Will it increase, decline or stabilize? (ii) What are the likely future trends of processed palm oil exports? Will it increase exponentially, stabilize or decline? To answer these questions, a system dynamics model was developed for the Malaysian palm oil. Application of the system dynamics model provides a framework to understand the feedback structure and how changes in variables impact the behavior of the palm oil industry. New planting, oil palm immature area, mature area, total planted area, production, crude palm oil price, crude palm oil export and processed palm oil export are simulated under four policy scenarios. This research suggests that with low crude palm oil export duties, the crude palm oil domestic price, profitability of plantation owners, immature crop, mature crop, total planted area, production and exports of crude palm oil are expected to increase, while the exports of processed palm oil is expected to decline.